COMBUSTION, PERFORMANCE, AND EMISSIONS CHARACTERISTICS OF SYNGASES IN A DIRECT-INJECTION SPARK-IGNITION ENGINE - HAGOS, FTWI YOHANESS (2013)
Syngas from biomass gasification is a carbon neutral fuel. It was in use at the WWII era before being replaced by gasoline. This fuel is hypothesized technically and economically competitive to compressed natural gas (CNG) for use as a fuel in modern spark-ignition (SI) engines. However, such fuel has never been investigated in direct-injection (OJ) Sl engines. The aim of the study was to experimentally investigate combustion, performance, and emissions characteristics of different syngases. A four-stoke, single-cylinder, Dl Sl engine originally designed for CNG was used at wide open throttle position for speeds ranging from 1500-2400 rev/min. The ignition advance was set at maximum brake torque (MBT).